Σχεδιασμός, παραγωγή και εκπαιδευτική αξιοποίηση της ψηφιακής αφήγησης - Σοφός , Αλιβίζος (Λοΐζος); Γιασιράνης , Στέφανος (Open Journal of Animation, Film and Interactive Media in Education and Culture [AFIMinEC], 2023)
Digital storytelling can create opportunities for effective learning, but it will by no means revolutionize teaching, as teaching as a process is broader and much more than a book, a video, a digital story, a lecture, or an exercise. Digital storytelling helps teach as much as text in books. This finding is usually not taken into account. On the one hand, we see that efforts to digitize narratives by many agencies are often no more than the creation of educational videos in conjunction with the hope that a new learning culture can emerge from them. On the other hand, we notice that many teachers are reluctant to use it in their lessons or to guide their students, mainly because they don’t know methodologies that would help them to include them in a meaningful way in the educational process. In this article, a brief introduction to digital storytelling is given. Then the basic knowledge (principles, steps, structuring, etc.) that a teacher must have in order to develop digital storytellings himself or to guide students effectively to do so, focusing on the structuring models of the narrative, are presented. Finally, the article focuses on the educational activities accompanying the digital storytelling to strengthen the learning process.